TREATISE OF IBERIAN KINGS AND RUSSIAN-AUSTRIAN PROJECT FOR THE REDISTRIBUTION OF EUROPE - Natsvaladze , Mamuka (Collection of scientific papers «ΛΌГOΣ», 2023)
The present study is the first attempt in historiography to evaluate the Treatise of Iberian Kings, signed in 1790, within the context of the international political processes of the corresponding period. Development of the events in the Georgian political field and the need for a documentary declaration of military-political unity can be explained only by the Greek Project - the Austrian-Russian project of the redistribution of Europe in the 70-the 90s of the XVIII century.The article shows that the declaration of the unity of the Georgian political space became necessary during the truce negotiations with the Ottoman Empire in 1791 in Yasa. Based on the referred document, Russia should have declared a united Georgia as a separate buffer political space together with the Dacian Kingdom and the Greek Empire in accordance with the structure of the Greek Project. It is stated, for the first time in historiography that the need to sign the Treatise of Iberian Kings is directly related to the truce negotiation process during the Russian-Ottoman war. Hence, the Georgian political spectrum had claims to return Adjara and Samtskhe Saatabago during the process of possible redistribution of the Ottoman Empire,